2009
DOI: 10.1007/s10648-009-9097-8
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Educational Applications of Mental Simulation: A Meta-review

Abstract: This paper focuses on the potential of Mental Simulation (mentally rehearsing an action to enhance performance) as a useful contemporary educational method. By means of a metareview, it is examined which conditions impede or facilitate the effectiveness of Mental Simulation (MS). A computer search was conducted using Ovid PsycINFO. Reviews, metareviews or meta-analyses published between 1806-2006 were included. The current paper presents the results of 10 publications in which about 630 studies on mental simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Implementation intentions benefit subsequent prospective memory performance by increasing the probability that when the future context is encountered, the intended action is triggered (e.g., Chasteen, Park, & Schwarz, 2001), and recent evidence indicates that mental simulations contribute significantly to the effectiveness of implementation intentions (Brewer & Marsh, 2010; Papies, Aarts, & De Vries, 2009). These findings documenting beneficial effects of simulations on prospective memory complement a large research literature demonstrating that imagining carrying out various kinds of skills – ranging from athletic acts to surgical procedures – can produce significant benefits on their later performance (e.g., Arora et al, 2011; Taylor et al, 1998; van Meer & Theunissen, 2009). …”
Section: Future Event Simulation: the Case For Adaptive Functionsupporting
confidence: 71%
“…Implementation intentions benefit subsequent prospective memory performance by increasing the probability that when the future context is encountered, the intended action is triggered (e.g., Chasteen, Park, & Schwarz, 2001), and recent evidence indicates that mental simulations contribute significantly to the effectiveness of implementation intentions (Brewer & Marsh, 2010; Papies, Aarts, & De Vries, 2009). These findings documenting beneficial effects of simulations on prospective memory complement a large research literature demonstrating that imagining carrying out various kinds of skills – ranging from athletic acts to surgical procedures – can produce significant benefits on their later performance (e.g., Arora et al, 2011; Taylor et al, 1998; van Meer & Theunissen, 2009). …”
Section: Future Event Simulation: the Case For Adaptive Functionsupporting
confidence: 71%
“…Implementation intentions benefit subsequent prospective memory performance by increasing the probability that when the future context is encountered, the intended action is triggered (e.g., Chasteen, Park, & Schwarz, 2001), and recent evidence indicates that mental simulations contribute significantly to the effectiveness of implementation intentions (Brewer & Marsh, 2010;Papies, Aarts, & De Vries, 2009). These findings documenting beneficial effects of simulations on prospective memory complement a large research literature demonstrating that imagining carrying out various kinds of skills -ranging from athletic acts to surgical procedures -can produce significant benefits on their later performance (e.g., Arora et al, 2011;Taylor et al, 1998;van Meer & Theunissen, 2009). …”
Section: Future Simulations Can Enhance Prospective and Retrospectivesupporting
confidence: 70%
“…Mental rehearsal was used because previous studies have demonstrated it can facilitate learning (Cooper, Tindall-Ford, Chandler, & Sweller, 2001;Ginns, Chandler, & Sweller, 2003;Ginns, 2005b;Leahy & Sweller, 2004, 2008Renkl, Stark, Gruber, & Mandl, 1998;Tindall-Ford & Sweller, 2006;Van Meer & Theunissen, 2009). Mental rehearsal is particularly applicable to students who have a degree of prior knowledge in the content domain and so are capable of imagining concepts and procedures.…”
Section: Methodsmentioning
confidence: 99%